Performance of pineapple slips inoculated with diazotrophic phosphate-solubilizing bacteria and rock phosphate - Lílian Estrela Borges Baldotto (Revista Ceres, 2014)
Besides fixing N 2 , some diazotrophic bacteria or diazotrophs, also synthesize organic acids and are able to solubilize rock phosphates, increasing the availability of P for plants. The application of these bacteria to pineapple leaf axils in combination with rock phosphate could increase N and P availability for the crop, due to the bacterial activity of biological nitrogen fixation and phosphate solubilization. The objectives of this study were: (i) to select and characterize diazotrophs able to solubilize phosphates in vitro and (ii) evaluate the initial performance of the pineapple cultivars Imperial and Pérola in response to inoculation with selected bacteria in combination with rock phosphate. The experiments were conducted at Universidade Estadual do Norte Fluminense Darcy Ribeiro, in 2009. In the treatments with bacteria the leaf contents of N, P and K were higher than those of the controls, followed by an increase in plant growth. These results indicate that the combined application of diazotrophic phosphate-solubilizing bacteria Burkholderia together with Araxá rock phosphate can be used to improve the initial performance of pineapple slips.